2006
DOI: 10.1111/j.1742-7843.2006.pto_530.x
|View full text |Cite
|
Sign up to set email alerts
|

A Latex‐Induced Allergic Airway Inflammation Model in Mice

Abstract: Latex allergy is important due to serious health impacts and widespread use of its products. Latex allergic reactions can be induced in skin and mucosal surfaces including the respiratory tract. The development of murine models of allergic airway inflammation has provided a framework to dissect out the cellular and molecular mechanisms of allergic respiratory inflammation. In this study we have developed a new mouse model of latex allergic airway inflammation using aerosol inhalation. The allergic inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A study by Raulf-Heimsoth et al, 17 which suggested cytokine increases due to latex exposure, reported that 32 health care professionals with suspected latex allergies had increased IL-5 levels in the nasal wash and nasal swab. Farzaneh et al 18 showed that latex allergen inhalation elevates IL-5 and IL-13 levels in bronchoalveolar lavage in mice. The present study investigated whether intense and long-term latex contact in employees with chronic latex exposure affects serum cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Raulf-Heimsoth et al, 17 which suggested cytokine increases due to latex exposure, reported that 32 health care professionals with suspected latex allergies had increased IL-5 levels in the nasal wash and nasal swab. Farzaneh et al 18 showed that latex allergen inhalation elevates IL-5 and IL-13 levels in bronchoalveolar lavage in mice. The present study investigated whether intense and long-term latex contact in employees with chronic latex exposure affects serum cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of variations of this model in mice using extracts of different allergens, such as cockroach extract [131], common ragweed extract [132], latex extract [133] (as of today seldom used as an asthmatic model) and extracts from several Aspergillus species, mainly fumigatus [134]. Additionally, a combination of HDMs, ragweed, and Aspergillus fumigatus extracts called DRA is also used to induce chronic asthma in mice, closely mimicking human asthma.…”
Section: House Dust Mite (Hdm) and Other Allergenic Extract-induced A...mentioning
confidence: 99%
“…2). Experimental models of latex allergy allow investigation of allergen forms, routes of sensitization, mechanisms of down-regulating the adverse immune response to allergens and evaluation of novel specific treatments [129][130][131][132][133][134].…”
Section: Specific Immunotherapy For Latex Allergy -Current Statusmentioning
confidence: 99%